The Influence of Simpler Application on Students’ Vocabulary Mastery of Junior High School in Indonesian - Dea Shakila; Jumbuh Prabowo; Ledy Nurlely (Journal of Linguistics, Literacy, and Pedagogy, 2026)
The objective of this research was to assess students’ vocabulary mastery using the Simpler application. The research employed a quasi-experimental design, with cluster random sampling. The study selected two classes: the control class (N=30) and the experimental class (N=32) at the seventh grade of a junior high school in Serang regency. Data were collected through pre-test and post-test, and analyzed using the t-test with the SPSS v25 program. While the control class had an improvement from 51.60 to 60.93, the experimental class saw a rise from 55.50 to 77.87. There was a statistically significant difference (p = 0.00) between the two groups in the post-test results. The results showed that the Simpler application has significantly improve the students’ vocabulary mastery and simple sentence production. This study sheds light on the potential of media in enhancing English language acquisition, specifically highlighting the beneficial effects of the Simpler application on vocabulary instruction.